Career Choice of The Students, What is Important? - Fien Zulfikarijah; Achmad Mohyi (Journal of Career and Entrepreneurship, 2022)
This study aims to determine the factors considered by students in choosing a career after graduating from college. The research population is students of the 4 largest universities in Malang, they are Brawijaya University, State University of Malang, University of Muhammadiyah Malang and State Islamic University of Malang. The sample of the study was 200 respondents with details of each university 50 respondents, respondents who filled out the complete questionnaire were 134. The analysis tool was factor analysis with 24 variables originating from the voice of respondents. From the data analysis process, 16 variables were worthy of analysis and grouped into 6 factors. The results showed that there were 6 factors for student career choice are: financial, job information, opportunity, social environment, challenge and interest, with financial being the dominant factor.